Concept of Cutaneous T Cell Lymphoma in Ayurveda Perspective and its Management by Sodhana, Samana and Rasayana: A Review Article (International Journal of Ayurveda and Pharma Research, 2022)
Cutaneous T cell lymphoma (CTCL) are a rare group of diseases caused by uncontrolled proliferation of T cells which belongs to mature T cell lymphoma having indolent nature. Two thirds of the CTCL are comprised of Mycosis Fungoides (MF) and Sezary Syndrome (SS). They are characterized by macules and patches which on later progresses to tumors or nodules with adenopathy and other organ infiltration. If left untreated the risk of developing infection increases with visceral involvement of skin, GI tract, lungs and adrenals. Diagnosis is done by histopathological appearance, cytogenetic analysis, etiology and the functional biology of neoplastic cells. Imaging techniques (MRI and CT) are widely done to assess the staging of disease and other tissue involvement. Radiotherapy, chemotherapy and retinoids have been in use since long time, but possess many side effects. According to Ayurveda, CTCL can be caused by Ahara like Virudha, Agantuja bhavas, Beeja-beejabhaga-beejabhagavayava dushti and Ojas/bala hani. The clinical features can be related with Kushta and in later stage simulates Dhatugata kushta and Granthi-arbuda. The etiopathogenesis of CTCL can be considered as formation of Ama, Agnimandhya, Srothovaigunya, and Balahani. Management will be preventive, curative and palliative with Sodhana, Samana and Rasayana therapies